Writing for scholarly publication : behind the scenes in language education - Casanave, Christine Pearson, 1944-; Vandrick, Stephanie (L. Erlbaum Associates, 2003)
This collection of first-person essays by established authors provides a wealth of support and insights for new and experienced academic writers in language education and multicultural studies.